The transfer of human resource management practices to Brazil: a practical assessment and theoretical test of portability - Stephen, David W., author; Gloeckner, Gene W., advisor (Colorado State University. Libraries, 2000)
Human resource management (HRM) practices may contribute to a firm's competitive advantage. HRM theories and practices developed in North America are laden with culturally bound values, perspectives, and expectations. When a multinational enterprise (MNE) attempts to transfer HRM practices and policies to a foreign operation abroad, or when a foreign firm attempts to import HRM practices from abroad, the cultural values inherent in the practices may not fit the foreign cultural environment. Fifteen interviews with Brazilian HRM practitioners and academicians were conducted in Brazil to elucidate what practices are appropriate to the Brazilian environment and what theories seem to support those practices. Findings of the study indicate that importation of American management models and practices are common in Brazil but that adaptations must be made in order to make practices fit the economic, political, and cultural environments. The unique Brazilian environment and examples of transference are assessed and described by the informants. Successful importation of foreign models and practices requires "cannibalism," or organic metabolization, by the local culture. A Brazilian theoretical model of "strategic anthropophagia" illustrates this metabolization. An original model is presented to test the portability of the transfer of management practices, based on the anthropophagus theory. Conclusions assert that the Brazilian model of strategic anthropophagia and the test of portability are methods that are congruent with the essential criteria for developing strategic HRM practices that contribute to developing a competitive advantage in Brazil.
Keywords: minority and ethnic groups; sociology; cultural relations; studies; research; language; accuracy; success; managers; communication; credibility; influence; interviews; American culture; ethnic studies; bias; perceptions; planning; decision making; copyright; cultural differences; attitudes